Herbert Marcuse vs Michel Foucault. On How Outsiders Changed the Western Culture in the 1960s and the 1970s (in Polish) (Diametros, 2016)
The aim of the article is to compare the ideas of Herbert Marcuse and Michel Foucault. In his works Marcuse focused on the excluded social circles. Their revolt against the establishment shook up the normative foundations of the social order in the 1960s and the 1970s, which finally led to a cultural revolution. Inspired by these social changes, Foucault was interested in the effects of this revolution at the epistemological and moral level. He recognized that the actions of the excluded circles weakened the institutional order which hitherto tempered the development of the alternative forms of knowledge and lifestyle in the western culture. Hence the contemporary western culture is a place of relentless conflicts between different values and conceptions of truth, but also a place of unique tolerance and a variety of lifestyles.
Keywords: outsiders; cultural revolution; establishment; the revolt of knowledge; morality; social order; social praxis